2017
DOI: 10.1136/bjophthalmol-2016-309208
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between central visual field sensitivity and macular ganglion cell/inner plexiform layer thickness in glaucoma

Abstract: NCT01742819.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
45
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 26 publications
7
45
0
1
Order By: Relevance
“…Studies have explored structure-function relationships between various glaucoma outcome measures and threshold sensitivity in visual field testing. 23,24 We have evidence here that correlations of macular GCC thickness with VFs are comparable to those of peripapillary RNFL with VFs. Strictly GCC does not solely reflect loss of ganglion cells as the measure of GCC is a combination of RNFL, ganglion cell layer and inner plexiform layer.…”
Section: Discussionmentioning
confidence: 53%
“…Studies have explored structure-function relationships between various glaucoma outcome measures and threshold sensitivity in visual field testing. 23,24 We have evidence here that correlations of macular GCC thickness with VFs are comparable to those of peripapillary RNFL with VFs. Strictly GCC does not solely reflect loss of ganglion cells as the measure of GCC is a combination of RNFL, ganglion cell layer and inner plexiform layer.…”
Section: Discussionmentioning
confidence: 53%
“…In that study, macular GCIPL thickness reflected macular functional damage well in more advanced glaucoma, the stage wherein structural change is thought to be less sensitive and informative for indicating disease status. Recently, a pattern of correlation between GCIPL thickness and 10-2 SAP test points, presented by Lee et al , showed localised arcuate characteristics in the central macula, which were well matched with the patterns of GCIPL defect themselves 39. All of the reports above noted have provided strong evidence that VF function can be relatively well inferred from macular parameters, especially in the central macular region.…”
Section: Introductionmentioning
confidence: 67%
“…Other studies relied on different types of OCT inputs to get predictions of SAP. 7,[33][34][35][36][37] Christopher et al 37 achieved best performance when using en face images to predict SAP global metrics and sectoral averages. It should be noted, however, that our main purpose was to use the CNN to develop an SF map.…”
Section: Discussionmentioning
confidence: 99%